Pengaruh Overhaul Terhadap Efektifitas Kondensor Di PT. Indonesia Power Up Suralaya Unit III - Halim Rusjdi; Achmad Ghozali; Nofirman Nofirman (JURNAL POWERPLANT, 2020)
In the power plant there are important component, it is condenser. A condenser has function to condense LP turbine exhaust vapor foe condensation.This time the author this time only includes calculations,to find out the total heat transfer using the log mean temperature Difference (LMTD) Method and Number Of Transfer Unit(NTU) in condenser unit III. Inthis research method the author can describe the heat transfer in the condenser what happens before andafter overhaul. It is expected that the resultsof the condition after overhaul must be better than before the overhau.The value of the condenser efficiency calculation of the effectiveness before and after overhaul experienced the highest increase on day 4 from 65.6% to 73.5% increase in condenser efficiency of 7.83%.